Non‐radiation endoscopic retrograde cholangiopancreatography in the management of choledocholithiasis during pregnancy. Issue 6 (26th May 2014) - Wu, Wenming; Faigel, Douglas O.; Sun, Gang; Yang, Yunsheng
<x xml:space="preserve">Abstract</x> Gallstone diseases are common during pregnancy. In most cases, patients are asymptomatic and do not require any treatment. However, choledocholithiasis, cholangitis, and gallstone pancreatitis may potentially become life‐threatening for both mother and fetus and often require urgent intervention. Although endoscopic retrograde cholangiopancreatography (ERCP) has become the standard technique for removing common bile duct stones, it is associated with ionizing radiation that could carry teratogenic risk. Non‐radiation ERCP (NR‐ERCP) is reported to be effective without incurring this risk. Two techniques have been described to confirm bile duct cannulation: bile aspiration and image guidance. With bile aspiration, biliary cannulation is confirmed by applying suction to the cannula to yield bile, thus confirming an intrabiliary position. Image guidance involves using ultrasound or direct visualization (choledochoscopy) to confirm selective biliary cannulation or duct clearance. Once cannulation is achieved, the stones are removed using standard ERCP techniques and tools. Case series and retrospective studies have reported success rates of up to 90% for NR‐ERCP with complication rates similar to standard ERCP. Pregnancy outcomes are not adversely affected by NR‐ERCP, but whether the avoidance of radiation carries benefit for the baby is unknown. Prospective comparative trials are lacking. NR‐ERCP is technically demanding and should be attempted only by skilled biliary endoscopists in properly equipped and staffed health‐care institutions, in a multidisciplinary setting.